KONSEP MANUSIA DALAM PEMIKIRAN IBNU KHALDUN - M. Riza Chamadi (CV. Amerta Media, 2017)
Humans are unique creatures, possessing two elements that are physical and spiritual. The two elements need to be further explored in the human concept. Al-Quran divides human into four categories, namely An-Nas, Basyar, Man, and Insan. in the frame of Ibn Khaldun's thinking, he describes human beings into two categories as commonly as human beings as a physical and spiritual form. Ibn Khaldun then describes with various approaches and analysis is so beautiful that suggests that humans are creatures of intellect and traditional creatures.Key Words: Human, al-Qur'an, Ibn Khaldun